The lexical unit crush and its uses: English, Brazilian Portuguese and French - De Paula Molinari, Milena [UNESP]; Demarque, Estela [UNESP]; Da Silva, Maria Cristina Parreira [UNESP] (Universidade Estadual de Maringa, 2019)
With the globalization and the easy access to the Internet, it is known that today there is a shortening of distances due to increase of the use of technologies, mainly through social networks. The purpose of this article is to study the use of the lexical unit crush, an English word, that through media such as Facebook, Instagram, Twitter, etc., is becoming increasingly popular in other languages, such as in Brazilian Portuguese and in French. To accomplish this research, the Lexicology was a theoretical contribution, more specifically the studies about the loan words, foreignisms (Silva 2006) and neologisms (Alves, 1996). This article is also based on Corpus Linguistics (Berber Sardinha, 2004), for the selection and processing of the whole corpora necessary for this study. The tool BootCat (Baroni & Bernardini, 2004) carried out the raising of the corpora in English, Brazilian Portuguese and French. In order to analyze the use of the lexical unit crush in these three languages. According to our research, we found that the English UL can already be considered as a loan in Brazilian Portuguese that is about to adapt syntactically. Thus, the UL is no longer considered a loanword in Brazilian Portuguese, but a neologism.
A unidade lexical crush e seus usos: Inglês, português do Brasil e francês
Keywords: English language; French language; Loan; Neologisms; Portuguese language